The Impact of Multiculturalism on Trade in Medieval Islam: The Azerbaijani Case - Mirzabayova, Roya (Universitas Islam Negeri Sunan Kalijaga, 2024)
Islamic civilization in the Middle Ages, the period of cultural, economic, and scientific development called the